Pancytokeratin immunostained tumor buds and cytoplasmic pseudofragments are reliable early predictive variables for regional lymph node metastatic risk assessment of oral squamous cell carcinoma - S V Sowmya; Roopa S Rao; Kavitha Prasad (Wolters Kluwer Medknow Publications, 2020)
Context: The 5-year survival rate in patients with cervical lymph node metastasis is reported to be 20-36% post surgery as compared to 63-86% in patients without nodal involvement. This necessitates assessing the metastatic potential of OSCC patients. Objectives: To evaluate the role of Pancytokeratin immunostained tumour buds and cytoplasmic pseudofragments with other histopathological and immunohistochemical variables in predicting metastatic risk of Oral Squamous Cell Carcinoma (OSCC). Settings and Design: Retrospective study on archival tissues of OSCC available from the Department of Oral Pathology and Microbiology. Methodology: Totally, 40 samples of 117 histopathologically diagnosed OSCC samples were selected that displayed metastatic risk variables like invasive tumour front pattern, lymphovascular invasion, tumour buds and cytoplasmic pseudofragmentation and were grouped into 20 each of metastatic and non-metastatic OSCC. 5 normal oral mucosa samples were included in the control group. The 45 tissues were stained with congo red to assess tumour - associated tissue eosinophilia (TATE) and immunohistochemically evaluated for tumour budding and cytoplasmic pseudofragmentation using pancytokeratin, proliferation (Ki-67), microvessel density (MVD)(CD31) and lymphatic vessel density (LVD)( LYVE-1). Statistical Analysis: Pearson's Chi square test and Man Whitney U test were used and analysed by Statistical Package for the Social Sciences (SPSS) software version 20.0. Results: Metastatic OSCC showed significantly high number of tumour buds (p = 0.001), cytoplasmic pseudofragments (p = 0.008), higher tumour grade (p = 0.038), lymphovascular invasion (p = 0.008) and LVD (p = 0.013), aggressive invasive tumour front pattern (p = 0.001) compared to non-metastatic OSCC. Conclusion: Pancytokeratin immunostained tumour buds, cytoplasmic pseudofragments and higher LYVE-1 expression may be used as independent predictors for OSCC metastasis. This study highlights the importance of recognizing the early metastatic risk variables that navigates the surgeon in planning appropriate therapy for OSCC.